Fatores que influenciam a internacionalização por e-commerce de calçados brasileiros para países da América do Sul - Reis, André Daudt dos (Universidade do Vale do Rio dos Sinos, 2018)
The research objective of this monography is to analyze the influence factors of the internationalization of e-commerce operations from the Brazilian footwear industry to South American countries, more specific to Argentina, Chile and Colombia. This study also seek to identify the main barriers for these companies internationalization, which are the control required by them and the more suitable entry mode proposal. To achieve these results, it was done a qualitative field research with a data collection composed by interviews with professionals specialized in electronic commerce in South America. Also, executives from the footwear industry, who work with their own branded products, have e-commerce operations in Brazil, are exporters to Argentina, Chile and Colombia and have interest in internationalize their e-commerce to those countries were interviewed. The results findings were that the external factors such as logistics and telecommunication infrastructure, related services, electronic payment options and consumer propensity were similar to the Brazilian standard. However, there were many discrepancies regarding local legislation, making it the main barrier for the internationalization of those companies. In addition, Brazilian companies demand a high-level control under the commercial and brand management, making the more suitable entry mode option the one with share control over the operation, like a licensing mode.
Keywords: E-commerce América do Sul; Internacionalização de e-commerce; Internacionalização da indústria calçadista; E-commerce para a indústria calçadista; E-commerce South American; E-commerce internationalization; Footwear industry internationalization; Footwear e-commerce; ACCNPQ::Ciências Sociais Aplicadas::Administração